Zielkonflikt zwischen Lärmschutz und Siedlungsverdichtung - Lüdi, Miriam (sui generis Verlag, 2023)
The conflict between settlement density and noise protection leads to challenges in spatial planning and construction projects. The pressure to densify settlements is constantly increasing. At the same time, traffic, everyday and leisure noise is becoming louder in many places and can prevent construction projects that would actually be suitable for densifying settlements. There are various calls for the conflict of objectives between noise protection and settlement densification to be better addressed in noise protection law is regulated. The Federal Council has submitted a draft decree and a message to amend noise protection law in the Environmental Protection Act referred to Parliament. Against this background, this book analyzes the current and future legal situation.